The influence of the time token type cooperative learning model on learning interest Akidah Akhlak - M. Indra Saputra; Siti Aprilia Sari; Deden Makbuloh (al-Iltizam: Jurnal Pendidikan Agama Islam, 2025)
This study aims to determine the effect of the Time Token type cooperative learning model on students' learning interest in the subject of Akidah Akhlak at MTs Darul Huda Bandar Lampung. This study uses a quantitative approach with a Posttest Only Control Group design, so as to be able to compare learning interest between the treated class (experiment) and the conventional class. The research instrument is a validated learning interest questionnaire. Data analysis was carried out using SPSS 25 through normality tests, homogeneity tests, and T tests to see statistical differences in results. The results showed that the Time Token learning model had a significant effect on increasing students' learning interest. The normality test showed that the data were normally distributed, while Levene's homogeneity test produced a significance value of 0.868, which indicated that the variance of the two groups was homogeneous. Based on the results of the Independent Samples T-Test, a t value of 2.156 was obtained with a degree of freedom (df) of 48 and a Sig. (2-tailed) value of 0.036, smaller than 0.05. These findings demonstrate a significant difference in average scores between the experimental and conventional classes. Thus, the Time Token model has proven more effective in increasing student learning interest than conventional learning.